ANALYSIS OF THE EFFECTIVENESS OF DIGITAL FLIPBOOK TEACHING MATERIALS USAGE BASED ON REALISTIC EDUCATION TO IMPROVE STUDENTS' COMMUNICATION ABILITY - Fitria Meisarah; Saeful Rohman; Rezki Akbar Norrahman; Reza Saeful Rachman; Hasim Hasim (Jurnal Scientia, 2023)
The lack of variety in the digital teaching resources that teachers utilize to facilitate learning in the digital era is what inspired this research. It is essential to create instructional resources that are relevant to students' daily lives. In addition, instructional materials that help improve students' mathematical skills are required. This study aims to provide digital teaching resources based on RME learning that can help students improve their mathematics communication abilities. The ASSURE model (Analyze Learners; State Objectives; Choose approach, Media, and Materials; Utilize Materials; Require Learners' Responses; Evaluate and Revise) was utilized in this study along with the R&D approach. This teaching material was tested on class junior high school students at a private school with a total of 30 students. The research results show that teaching materials meet the high suitability criteria in terms of content suitability, language, presentation, design, RME approach, mathematical communication, and evaluation. The teaching materials received a positive response from students, which met the appropriate criteria. After employing instructional materials, students scored an average of 76 on their ability to communicate mathematically. As a result, these teaching tools are deemed appropriate for use by teachers as extra learning resources.